Low-grade fibromyxoid sarcoma of the parapharyngeal space: an unusual location. Issue 5 (24th May 2021) - Deewani, Muhammad Hammad; Danish, Muhammad Hassan; Awan, Muhammad Sohail; Ud Din, Nasir
Abstract : Low-grade fibromyxoid sarcoma (LGFMS) is an uncommon soft-tissue malignancy. LGFMS preferentially affects trunks and extremities of young adults; however, occasional cases have been reported in different sites of head and neck region including oral cavity, larynx and oropharynx. LGFMS usually exhibit areas of collagenised and myxoid stroma with appearance of spindle cells in whorling pattern. It is a challenge to diagnose it accurately as most of the time it is misdiagnosed as benign neoplastic entity of spindle cells. There have been only few isolated cases of LGFMS reported in head and neck region and LGFMS originating from the parapharyngeal space has never been reported before. We recently experienced a case of low grade fibomyxoid sarcoma in parapharyngeal space of neck. LGFMS have the propensity to locally recur and to metastasise. Due to its rarity in head and neck region, there are no well-established treatment and follow-up guidelines.